Polymeric Insulation surface condition Analysis Using Linear Time Frequency Distributions - NORDDIN, NURBAHIRAH; Abdullah, Abdul Rahim; Zainal Abidin, Nur Qamarina; Aman, Aminudin; Ramani, Anis Niza (2013)
Polymeric insulator exposed to pollution leads to tracking and erosion affects their performance. There are no specific method to determine their service life. Most studies shows surface condition and their pollution severity of an insulator can be monitor by using leakage current frequency components. This paper presents linear time frequency distributions (TFDs) for leakage current of polymeric insulation for high voltage applications. Tracking and erosion test (Inclined Plane Test (IPT)) complying with BS EN60587-2007 is conducted on polymeric insulation to collect different leakage current patterns. Fast Fourier transforms (FFT) unable to provide temporal information and has limitation to analyze non stationary signal. To overcome this, time frequency distributions (TFDs) shown in time frequency representation (TFR) with temporal and spectral is used. The verification using both methods on several disturbances with known parameters have been made and mean absolute percentage error (MAPE) used to identify the accuracy of both methods. The parameters measured are root mean square (RMS), total harmonic distortion (THD),total non harmonic distortion (TnHD) and total waveform distortion (TWD) used to determine the best method to analyze leakage current. The comparison shows that s-transform provide better time and frequency resolution than spectrogram.